The Practice of Dividing the Heritage of the Burneh Community, Bangkalan: Between Customary Law and Islamic Law - Esa Nurlaili; Fenni Rahmawati; Satriya Ardhi Dwi Septiaji; Umi Indasyah Zahro (Yayasan Insan Mulia Bima, 2025)
This study aims to analyze the practice of inheritance distribution in Burneh Village, Bangkalan Regency, focusing on the interaction between Islamic inheritance law and local customary law. The main issue examined is how the people of Burneh implement faraidh provisions in daily life and to what extent local traditions influence inheritance practices. The research employed a qualitative approach using in-depth interviews with religious leaders, customary leaders, and several household heads. The findings reveal that inheritance distribution in Burneh generally does not strictly follow faraidh regulations but instead emphasizes family deliberation and mutual consent. Equal distribution between male and female heirs is often chosen to maintain harmony, while some testators also distribute assets through hibah (gifts) before death. The conclusion of this study indicates that inheritance practices in Burneh reflect a form of legal pluralism that prioritizes social harmony and communal welfare, while simultaneously demonstrating a creative adaptation between Islamic legal norms and local wisdom.